Sistem Pemantauan dan Pengendalian Debit Fluida Berbasis Arduino dan Website - Noviana Widyaningrum; Unan Yusmaniar Oktiawati (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2020)
IoT can combine hardware and software for communication between them. The application of this system can be done on a solenoid valve to regulate the flow via online, which can be varied based on current temperature. The fluid flows are validated with a flow meter sensor that sends data to a server to decide whether the flows need to be added to the furnace or not. There is a database server that stores data in cloud from sensors so that the system can run realtime. The system is displayed on a website with dashboard display regarding the flow and the condition of the valves in realtime. In testing, black box testing is used to make more use of functional things in the system designed for the convenience of users of fluid flow monitoring and control, based on the appearance of the website used, the functions available, the results of the sensors provided, and the data transmission process that is running. Furthermore, the system can show that the function of the hardware or website to monitor and control fluid discharge has been running well and can be used by users easily and beneficially.